Salt Tolerance of Some Arhar (Cajanus Indicus) and Cowpea (Vigna Cinencis) Varieties at Germination and Seedlings Stages - Paliwal, K V; Maliwal, G L (Annals of Arid Zone, 2016)
Twenty three varieties of Arhar(Cajanus indicus) and fourteen of Cowpea (Vigna cinencis) were screened for their salt tolerance characteristics at germination stage at five levels, (3, 6,Â·9. 1, 12 and 18 mmhos/cm) of salinity, Studies were conducted in plastic containers in quartz, and salts of sodium and calcium as their chlorides in the ratio of 4: I were used. Germination count was made after every 24 hrs and up to 240 hr The germination percentage and the height of the seedlings decreased with the increase of salinity. Varieties showed significant differences in their salt tolerance behaviour in germination and elongation of shoots. Most of ..4,,1uw and Cowpea varieties are salt tolerant from 6 to 12 mmhos/cm. In general, arhar is more salt tolerant than cowpea.